Repeatability of airway resistance measurements made using the interrupter technique. Issue 4 (1st April 2003) - Chan, E Y; Bridge, P D; Dundas, I; Pao, C S; Healy, M J R; McKenzie, S A
Abstract : Background: To be able to interpret any measurement, its repeatability should be known. This study reports the repeatability of airway resistance measurements using the interrupter technique (Rint) in children with and without respiratory symptoms. Methods: Children aged 2–10 years who were healthy, had persistent isolated cough, or who had previous wheeze were studied. On the same occasion, three Rint measurements were made 15 minutes apart, before and after placebo and salbutamol given in random order. Results from those given placebo first were analysed for within-occasion repeatability. Between-occasion repeatability measurements were made 2–20 weeks apart (median 3 weeks). Results: For 85 pairs of measurements before and after placebo the limits of agreement were 20% expected resistance and were unaffected by age or health status. The change in resistance following bronchodilator in one of 18 healthy children, 12 of 28 with cough, and 22 of 39 with wheeze exceeded this threshold. For between-occasion measurements the limits of agreement were 32% in 72 healthy subjects, 49% in 57 with cough, and 53% in 95 with previous wheeze. Conclusion: The measurement of airways resistance by the interrupter technique is clinically meaningful when change following an intervention such as the administration of bronchodilator is greater than its within-occasion repeatability. Between-occasion repeatability is too poor to judge change confidently.